Hubungan Kemandirian Belajar dengan Kemampuan Berpikir Kritis pada Mahasiswa - Idza Pamalah, Mar’a; Titi Pratitis, Niken; Kusumandari, Rahma (Green Publisher Indonesia, 2025)
Critical thinking skills are an important aspect for students in facing academic and professional challenges, but there are still many students who have difficulty developing these skills. This study aims to analyze the relationship between learning independence and critical thinking skills in students. The novelty of this research lies in the exploration of the factor of learning independence as the main predictor of increasing critical thinking in the context of higher education. This study uses a quantitative approach with a correlational method. The research sample consisted of 160 students who were selected through accidental sampling techniques. Data were collected using the learning independence scale and the critical thinking scale, which were analyzed using the Spearman Rho correlation test. The results showed that there was a positive and significant relationship between learning independence and critical thinking ability with a correlation value of 0.465 and a p-value of 0.000 (p < 0.05). These findings indicate that the higher the student's learning independence, the higher the critical thinking ability. The implications of this research can be used as a basis for educational institutions in designing learning strategies that encourage learning independence to improve students' critical thinking skills.